Religious Therapy Approaches and Framework for Psychological Condition and Spiritual Well-Being of Muslim Flood Victims - Husni binti Mohd Radzi (Universiti Sains Islam Malaysia, 2024)
The impact of floods on those who experience them can pose substantial social and mental health problems. The negative psychological effect of flood on the victimmust be overcome by appropriate coping skills. Many studies have showed that religious coping strategies have positive influence over of general health and emotional well-being.This study investigates (1) the relationship between religious coping with depression,stress and anxiety (2) to measure the relationship between depression, anxiety and stress with spiritual wellbeing and to (3) to measure the moderating factors of demographic influence (age,education and income) on the relationship between depression, anxiety and spiritual wellbeing. This study are also (4) to identify the dominant religious coping pattern (negative and positive religious coping, Muslim religious personality and religious ritual) and an integration of three religious counselling theories namely Religious Cognitive-Emotional Theory, Religious Cognitive Behaviour Theory and Ad-Din Cognitive Psychology as a counselling theoretical framework in the religious coping of the victims. Seven hypothesis were formed for this study.The quantitative analysis supported five out of seven research hypothesis.The study uses a set of questionnaires that was adapted from five inventories: DASS is to measure depression,anxiety and stress while Flood Spiritual Well-Being (FSWB)is to measure spiritual well-being. Brief Religious Coping (BRCOPE),Muslim Religious Personality Inventory (MPRI), Religious Ritual (RR) are instruments used to measure religious copings; BRCOPE is used to measure negative and positive religious coping.MPRI is to measure Muslim religious personality and RR is measuring religious rituals.This study is carried out on 1194 samples from four flood hit states which are Kelantan,Terengganu, Pahang and Selangor using convenient random sampling.The result of the study using SEM analysis showed (1) a negative significant correlation (-0.22 BRCOPE.-0.11 MRPI and -0.07, RR) between religious coping and depression, anxiety and stress. (2) Depression, anxiety and stress also showed negative significant correlation (-0.08) with spiritual wellbeing.The result proved that only age is significant moderators in the relationship between depression, anxiety and strees and spiritual well-being.Positive and negative religious coping is identified as the dominant coping strategies and are used widely by the Muslim flood victim,followed by Muslim Religious personality and religious ritual.The study also validates the Religious Cognitive- Emotional Theory,Religious Cognitive Behaviour Theory and Ad-Din Cognitive Psychology counselling theoretical framework in the religious coping of the victims. Research contribution on the aspects of theoretical and contextual to the religious and spiritual coping of flood victim and research implications are also discussed in this study.